Association Between Infectious Agents and Lesions in Post-Weaned Piglets and Fattening Heavy Pigs With Porcine Respiratory Disease Complex (PRDC) - Ruggeri, Jessica; Salogni, Cristian; Giovannini, Stefano; Vitale, Nicoletta; Boniotti, Maria Beatrice; Corradi, Attilio; Pozzi, Paolo; Pasquali, Paolo; Alborali, Giovanni Loris (Frontiers in Veterinary Science, 2020)
Porcine Respiratory Disease Complex (PRDC) is a multifactorial syndrome that causes health problems in growing pigs and economic losses to farmers. The etiological factors involved can be bacteria, viruses, or mycoplasmas. However, environmental stressors associated with farm management can influence the status of the animal’s health. The role and impact of different microorganisms in the development of the disease can be complex, and these are not fully understood. The severity of lesions are a consequence of synergism and combination of different factors. The aim of this study was to systematically analyse samples with a standardised diagnostic protocol in case of suspected PRDC. During necropsy, the lungs and carcasses were analysed to determine the severity and extension of lesions. Gross lesions were classified according to a pre-established scheme adapted from literature. Furthermore, pulmonary, pleural, and nasal lesions were scored to determine their severity and extension. Finally, the presence of infectious agents was investigated to identify the microorganisms involved in the cases studied. During the years 2014–2016, 1658 samples of lungs and carcasses with PRDC were analysed; among them 931 and 727 samples were from weaned piglets and fattening pigs, respectively. The most frequently observed lesions were characteristic of catarrhal bronchopneumonia, broncho-interstitial pneumonia, pleuropneumonia, and pleuritis. Some pathogens identified were correlated to specific lesions, whereas other pathogens to various lesions. These underline the need for the establishment of control and treatment programmes for individual farms.